Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content: 1. Kindergarten teachers practice in Hafar Al-Batin for active learning strategies Mrs. Ghada Ahmed Aljurbua 2. The Effectiveness of A Teaching Program Based on Some of Principles of TRIZ Theory for Teaching Science in The Development of Reflective Thinking Skills at The 2nd Intermediate Grade Students Mr. Waleed Saleh Alzaidi , Prof. Naif Abdulaziz Almutawa 3. The role of the Islamic education teacher in developing the values of moderation and moderation among secondary school students in Jeddah Mr. Fahad Ahmed Alomari , Prof. Habba Ahmed Akram 4. Effect of Employing Micro-Learning in an E-learning Environment on Correcting Spelling Errors Among Middle School Students Mrs. Al-Jawhara Naif Al-Shaibani , Co-Prof. Abdellraouf Mohamed Mohamed Ismail 5. Models and Strategies when Effective use of Electronic Games in Teaching English Vocabulary Dr. Afrah Haft Alawaty , Mrs. Somaya Suleiman Abu Zahra 6. A proposal to Add a Scholarship Unit for Islamic Education Curriculum for third Secondary Students According to Schools Promoting Positive Behavior in View of the Kingdom’s Vision 2030 Mrs. Najwa F. Idrees 7. The Effectiveness of Rotation of Stations Model for Blended learning in Developing the Creative Thinking Skill "Evaluating and Improving Ideas" in the Light of the PISA Framework for Mathematics Among Second- Grade Students Mrs. Amerh Owud Onallah Alsulmi